KETERAMPILAN MENULIS KARYA ILMIAH SISWA KELAS XI JURUSAN VOKASI DI MAN 2 BANYUMAS - Sesaria, Rahmadani; Yulianti, Uki; Nugroho, Bivit (LPPM Universitas PGRI Silampari Lubuklinggau, 2025)
Scientific writing skills are one of the important skills that students need to have, especially vocational students, because scientific writing skills are needed in the workplace and train critical, systematic, and logical thinking. However, many students still experience difficulties in writing scientific papers, both in terms of writing structure and linguistic aspects. This study aims to describe the scientific writing skills of grade XI vocational students at MAN 2 Banyumas in the 2024/2025 academic year based on the writing structure (beginning, main/content section, and ending section) and linguistic aspects (language variety, spelling, punctuation, cohesion, coherence, and main idea). These two aspects are listed in the learning objectives of scientific work material. The study used a descriptive qualitative approach with data collection techniques through documentation, observation, and interviews. The main data were seven student scientific papers in the form of papers. The results of the study indicate that in terms of writing structure, each data indicates that the components in the beginning, core/content, and end are incomplete. Similarly, many linguistic aspects, namely language variety, spelling, punctuation, cohesion and coherence, are still not fulfilled. Only two data have fulfilled the cohesion and coherence. And each data already contains the main idea. Thus, the scientific writing skills of vocational students from the writing structure and linguistic aspects have been fulfilled with an average achievement of 22.45%. This finding indicates that vocational students need guidance to be able to produce scientific papers that are systematically structured, have a complete writing structure, and comply with linguistic rules.